Estrategias de endomarketing y su influencia en la motivación de los colaboradores del banco Cencosud P-263 Paris, Trujillo, 2018 - Rodríguez Caspito, Hayri Licet (2021)
The main objective of this research was to determine the influence of Endomarketing on the motivation of Banco Cencosud P263 employees. That is why this thesis was aimed at demonstrating how Endomarketing proposals influence the motivation of an organization's collaborators, creating an adequate space where each worker feels satisfied, where collaborators are more productive and manage to develop professionally. In this sense, the variables studied were: Endomarketing Strategies and Motivation of the collaborators, for which a transactional correlational design was used. In addition, it is important to mention that the instrument used was the questionnaire, made up of 24 items on a Likert-type scale, applied to a sample of 13 bank workers. As the main results of the study, it was found that the factors that influence the motivation of Cencosud bank employees are: the remuneration they receive, the employment relationship with their immediate boss, security and stability, and personal development. Finally, to measure the correlation of the variables, the Pearson correlation test was used, concluding that there is a great influence of Endomarketing on the motivation of Banco Cencosud employees, with a significant degree of relationship of 0.797.